Tinjauan Yuridis Pelanggaran Hak Imigran Anak Dalam Kebijakan Zero Tolerance Amerika Serikat Dalam Perspektif HakAsasi Manusia Internasional - Yogi Alda Hijra; Evi Deliana; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Recent US policies have shown a shift in thinking from the concept of Universal Human Rightstowards the concept of human rights of citizens. By applying different standards to citizens and non-citizens.The President of the United States (Donald Trump) took action in the form of an entry ban for immigrantsfrom six countries to protect the United States from militant attacks. Donald Trump's policy is known as thezero tolerance policy. The zero tolerance policy adopted by Donald Trump in May resulted in all bordercrossers without official documents being criminally charged and imprisoned. Whereas their children(immigrants) are placed separately by their parents. They were taken to a place managed by the Ministry ofHealth and humanitarian services. They should not be treated with actions that conflict with the rules thatprotect the rights of the child.This study uses a normative legal research typology, which more specifically discusses the principlesof law. In this study the author uses the nature of descriptive research, because the author describes thereality investigated by researchers regarding children's rights violated by the United States through a zerotolerance policy. The results of the research conducted by the author are, the first zero tolerance policy is thecause of violations of the rights of child immigrants in the United States because of American presidentDonald Trump with children's rights that cannot be separated from his parents. Second, the internationalhuman rights perspective in resolving the problem of violations of child immigrant rights in the zerotolerance policy of the United States, namely that children have rights to be recognized in international law.Basically, human rights and children's rights must be respected and implemented.Keywords: Violations - Child Immigrant Rights - Zero Tolerance - International Human Rights